Inflammatory Burden Mapping as a Predictive Biomarker Framework for Population Health Transition - Jaksa, Suherman; Srisantyorini, Triana (Asian Journal of Healthcare Analytics, 2026)
The current transition in population health is characterized by an increase in chronic diseases related to inflammatory processes. Inflammation serves as a major biological mechanism linking environmental, metabolic, and disease risk factors in the population. Therefore, inflammatory burden mapping has the potential to be a predictive biomarker framework to understand the dynamics of public health changes. This research aims to develop a conceptual framework for Inflammatory Burden Mapping as a biomarker approach in predicting population health transitions. The study uses a conceptual analysis approach based on literature studies on various biomedical studies related to inflammatory biomarkers such as C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α). The results of the study show that the integration of inflammatory biomarkers with demographic and environmental factors can provide a comprehensive picture of the inflammatory burden in the population and help predict disease change patterns. This framework has the potential to strengthen public health monitoring systems and support the development of biomarker-based health intervention strategies.